Pengaruh Kualitas Pelayanan Dan Promosi terhadap Keputusan Menjadi Anggota dengan Minat Sebagai Variabel Intervening (Studi Kasus pada KSPPS BMT Sahabat Kita Semua) - Ai Nurasifa; Elis Nurhasanah; Heni Sukmawati (Prodi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2021)
This researcher aims to find out how the influence of service quality and promotion on the decision to become a member with interest as an intervening variable in KSPPS BMT Sahabat Kita All. Using quantitative descriptive method, the population is KSPPS BMT Sahabat Kita All members, while the number of samples is 96 respondents. The technique of collecting data is through questionnaires and using path analysis data analysis techniques using the Sobel test and F test. The results of the research are the variables of Service Quality, promotion, and interest with the effect of each variable being 23.1%, 24.9% and 17 ,7%. The results of the Sobel test show that service quality and promotion have a significant effect on the decision to become a member of KSPPS BMT Sahabat with interest as an intervening variable.